Constitutive overexpression of Qui-Quine Starch gene simultaneously improves starch and protein content in bioengineered cassava (Manihot esculenta Crantz) - Hankoua, Bertrand Bachaumond; Diao, Marieme; Ligaba-Osena, Ayalew; Garcia, Rafael A.; Harun, Sarahani; Ahlawat, Yogesh K. (Frontiers in Plant Science, 2025)
Cassava is a crucial source of daily calorie intake for millions of people in sub-Saharan Africa (SSA) but has an inferior protein content. Despite numerous attempts utilizing both traditional and biotechnological methods, efforts to address protein deficiency in cassava have met with little success. We aim to leverage modern biotechnologies to enhance cassava's nutritional value by creating bioengineered cassava cultivars with increased protein and starch content. In this study, we utilized Qui-Quine Starch (QQS), a novel orphan gene unique to Arabidopsis thaliana, to develop transgenic cassava plants with increased protein and starch accumulation in their tissues. A total of 10 independent transgenic cassava lines expressing QQS were successfully regenerated in this study, among which line R7 (F) demonstrated superior growth vigor. Quantitative RT-PCR verified the expression of the QQS gene in the transgenic lines. Data showed that QQS expression in cassava plants increased leaf protein content by 36% in line R’’’ (LA) L2 and root protein by 17% for the same line compared to their wild-type and empty vector (NPTII) control plants. Moreover, leaf-soluble total carbohydrates increased by 51.76% in line R (G) L2, and root-soluble total carbohydrates increased by 46.75% in line R7 (F). The novel function of QQS in increasing the starch content in the transgenic biomass is demonstrated. No significant change in the content of specific amino acids was observed among the lines and various plant parts. In addition, QQS expression revealed increased biomass, plant vigor, and early In vitro mini-tubers production for line R7 (F). Gene interaction study between AtQQS and 59 interacting partners generated 184 interactions or edges. These gene networks comprised several functional categories regulating the starch metabolic and auxin biosynthetic processes. The role of QQS in imparting starch and protein content of transgenic cassava plants is validated. The next logical step is the evaluation of biochemical profiles of cassava lines expressing QQS that reach maturity and the transferability of these findings to consumer-preferred cassava cultivars and local landraces grown in SSA. This study represents the first biotechnological report demonstrating a simultaneous increase of protein and starch content in bioengineered cassava.